'A Stronger Man and a More Virile Character': Australian Prime Ministers, Embodied Manhood and Political Authority in the Early Twentieth Century. Issue 4 (2nd October 2017) - Phillips-Peddlesden, Bethany
Abstract : In 1907 Andrew Fisher was evaluated as a 'stronger man  …  and more virile character' and therefore a better Australian Labor Party leader than Chris Watson. A key aspect of this assessment was his embodiment of respectable working-class manliness. One particularly overlooked aspect in the process of making men visible as men in Australian political history has been the male bodies of political leaders. This article offers the first systematic examination of the bodily practices and strategies of Alfred Deakin, George Reid and Andrew Fisher, three key players in the early formation of a two-party system in the decade following Federation. I seek to alter our understanding of political authority in the early federal period by examining how political contests played out using manhood – specifically, embodied manhood – as a key marker of political legitimacy.